Poor risk factor control in outpatients with diabetes mellitus type 2 in Germany: The DIAbetes COhoRtE (DIACORE) study - Rheinberger, Myriam; Lammert, Alexander; Krämer, Bernhard (PLOS ONE, 2019)
Introduction Patients with diabetes mellitus type 2 (DM2) are at high risk for micro- and macrovascular disease. Here, we explore the degree of traditional risk factor control in the baseline visit of a cohort of DM2 outpatients. Methods DIACORE (DIAbetes COhoRtE) is a prospective cohort study of 3000 adult DM2 outpatients. Here, we present results from the baseline visit. Sociodemographic and anthropometric variables, cardiovascular risk factors, comorbidities and medication were assessed by interview and medical exams. Serum-creatinine based estimated glomerular filtration rate (eGFRcrea) and urinary albumin-creatinine ratio (UACR) were determined for classification of chronic kidney disease (CKD). The proportion of patients with adequate control of traditional risk factors (blood pressure<140/90mmHg, HbA1c<7.5%, LDL<100mg/dl) was calculated in 2892 patients with non-missing data in 9 relevant variables within each KDIGO 2012 CKD class. Results In the analyzed baseline data (n = 2892, 60.2% men), mean (standard deviation) values for age, DM2 duration and HbA1c were 65.3 (9.3) years, 10.3 (8.4) years and 6.9% (1.1) respectively. Of these 2892 patients, 18.7% had CKD stage 3 or higher, 25.7% had UACR≥30mg/g. Adequate blood pressure, HbA1c and LDL control was achieved in 55.7%, 78.5% and 34.4%, respectively. In 16.4% of patients (473), all three risk factors were below recommended targets. The proportion of adequate risk factor control was similar across KDIGO eGFRcrea classes. Adequate blood pressure and HbA1c control were significantly associated with lower UACR category without and with controlling for other risk factors (p<0.0001, p = 0.0002, respectively). Conclusion In our study of patients with diabetes mellitus type 2, we observed a low level of risk factor control indicating potential for risk reduction.